Development of scheduling principles for Spoornet in Southern Africa - Dirkse van Schalkwyk, T. G.(Theunis Gysbert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing) -- University of Stellenbosch, 1999.